Crossed-beam and reduced dimensionality studies of the state-to-state integral cross sections of the Cl + HCD3(v) → HCl(v′) + CD3 reaction - Shan, X; Remmert, S; Clary, D; Zhang, B; Liu, K (2013)
The state-to-state integral cross sections of the Cl + HCD3(v) → HCl(v′) + CD3 reaction have been studied experimentally and theoretically. Reactions involving both Cl(2P3/2) and Cl(2P1/2) were analysed. In the experiment, a time-sliced velocity imaging detection method under crossed-beam condition was used. For theoretical study, a multiple potential energy surface model is employed. A combined reduced dimensionality quantum dynamics and quantum chemistry method is used with explicit treatment of spin-orbit coupling. Good agreement between experiment and theory is obtained, especially for the energy threshold dependence of the cross sections.© 2013 Elsevier B.V. All rights reserved2013 Elsevier B.V. All rights reserved.